Reverse matrix converter control method for PMSM drives using DPC - Bak, Yeongsu; Lee, Kyo Beum (International Journal of Electronics, 2018)
This paper proposes a control method for a reverse matrix converter (RMC) that drives a three-phase permanent magnet synchronous motor (PMSM). In this proposed method, direct power control (DPC) is used to control the voltage source rectifier of the RMC. The RMC is an indirect matrix converter operating in the boost mode, in which the power-flow directions of the input and output are switched. It has a minimum voltage transfer ratio of 1/0.866 in a linear-modulation region. In this paper, a control method that uses DPC as an additional control method is proposed in order to control the RMC driving a PMSM in the output stage. Simulations and experimental results verify the effectiveness of the proposed control method.
Keywords: Converter controls; Direct power control; Indirect matrix converter; Linear modulations; Permanent Magnet Synchronous Motor; Power conversion; Voltage source rectifiers; Voltage transfer ratio; AC/AC power conversion; boost-mode indirect matrix converter; direct power control; permanent magnet synchronous motor; reverse matrix converter